The complex effects of health-improving fitness on the physical condition of students - Кожокар, Kozhokar, Марина, Maryna; Vaskan, Ivan; Палагнюк, Palagniuk, Тарас, Taras; Zavgorodnia, Tetyana; Strazhnikova, Inna; Kyselytsia, Oksana; Balatska, Larisa; Yarmak, Olena (Journal of Physical Education and Sport, 2019)
The research presents the results of the pedagogical experiment, in which 58 students of Yuriy Fedkovych Chernivtsi National University of the city of Chernivtsi took part. The study is aimed to determine the complex effects of health-improving fitness on the physical condition of young men and girls. The program for physical education for first-year students, which included means of health-improving fitness was developed. The program was designed for one academic year (2018-2019). The study presents the results of the complex effects of health-improving fitness on the main components of the physical condition of young men and girls. The introduction of the proposed program in the process of physical education of students with healthimproving fitness means significantly (p <0.05; p <0.01) improves the functional ability of the cardiovascular system, manifests itself in an increase in adaptive potential capacity, a decrease in heart rate at rest by 10.6 % in young men and 10.9 % in girls, an increase in the level of physical performance according to indicators of the Ruffier index in boys by 47.0 % in boys and 38.4 % in girls and PWC170 in boys by 13.5 %, in girls by 10.1 %. The proposed program with health-improving fitness means increases the functional level of the respiratory system, in particular, the lung capacity in boys increased by 11.8 %, in girls - by 15.6 %, the Shtange test with breath-holding in boys improved by 23.0 % in girls by 16 5 %, the Genchi test improved in young men by 19.2 %. Health-improving fitness means have complex positive effects on the fundamental components of the physical condition of students.
Keywords: health-improving fitness, physical condition, students